SOCIAL MARKETING IN PUBLIC ADMINISTRATION OF SOCIAL SERVICE INSTITUTIONS - Bukanov, Hryhoriy; Kolesnyk, Alla; Tashkinova, Oksana; Kotlubai, Viacheslav; Koval, Viktor (Gênero & Direito, 2019)
The following conclusions can be drawn from the theoretical analysis and the results of the expert survey. Firstly, it is substantiated that social marketing is an effective mechanism for public administration of social organizations in Ukraine, and that public relations and social advertising are the leading technologies. Secondly, it is determined that the leading task of public relations in public administration is to develop concepts of social advertising and the formation of a positive image of the social service through information and advertising campaign on social services. Thirdly, it has been found that the more effective means of advertising the activities of social organizations are: TV and radio advertising; placement of articles in specialized (local printed) editions; booklets, memos, other handouts, and the main issues that should be covered in social advertising are: addiction, socio-economic problems, medical problems, problems of vulnerable sections of the population.